2016
DOI: 10.1097/mib.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of IBD Using High Definition Colonoscopes Does Not Miss Adenocarcinoma in Patients with Low-grade Dysplasia

Abstract: Background Historically, limits to the ability to detect dysplasia in chronic inflammatory bowel disease (IBD)-associated colitis resulted in the recommendation that neoplasia of any grade be treated by proctocolectomy. We hypothesized that with improved optical technologies, most neoplasia in colitis is now detectable and reassessed the prevalence of colitis-associated neoplasia. Methods We retrospectively reviewed all our patients with IBD who had pathologist-confirmed neoplasia on surveillance colonoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Two cohort studies and one case series reported on the rates of prevalent cancer found in the surgical colectomy specimen resected soon after a pre‐operative diagnosis of visible HGD where 94% 28 to 100% 29,30 had not been endoscopically resected pre‐operatively. The prevalent cancer rate varied from 0% (n = 0/26), 28 20% (n = 1/5) 30 to 35.8% (n = 34/95) 29 . The studies with the highest prevalent cancer rates only included cases where the dysplasia was located within the extent of inflamed mucosa, rather than proximal to it 29,30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two cohort studies and one case series reported on the rates of prevalent cancer found in the surgical colectomy specimen resected soon after a pre‐operative diagnosis of visible HGD where 94% 28 to 100% 29,30 had not been endoscopically resected pre‐operatively. The prevalent cancer rate varied from 0% (n = 0/26), 28 20% (n = 1/5) 30 to 35.8% (n = 34/95) 29 . The studies with the highest prevalent cancer rates only included cases where the dysplasia was located within the extent of inflamed mucosa, rather than proximal to it 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…The prevalent cancer rate varied from 0% (n = 0/26), 28 20% (n = 1/5) 30 to 35.8% (n = 34/95) 29 . The studies with the highest prevalent cancer rates only included cases where the dysplasia was located within the extent of inflamed mucosa, rather than proximal to it 29,30 . The pooled estimated cancer prevalence rate from all these studies was 13.7% (95% CI: 0.0%‐54.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Krugliak Cleveland et al [14] found no synchronous adenocarcinomas in patients who underwent colectomy for LGD at a single tertiary care center. In that study, only 1 out of 30 patients with LGD on colonoscopy was upstaged to HGD, and 3 additional patients were found to have one or more synchronous HGD lesions.…”
Section: Discussionmentioning
confidence: 99%
“…While studies included in this review lack specifics about the use of advanced surveillance (such as chromoendoscopy, narrow-band imaging or confocal endomicroscopy), the role of these and other visualization enhancement techniques should be explored to assess for a shift in colorectal neoplasia risks, with perhaps earlier detection and shortened inflammation exposure. 12 …”
Section: Discussionmentioning
confidence: 99%